A Comprehensive Approach to Cyber Resilience - Abraham, Chon; Abraham, Chon; Sims, Ronald (MIT Sloan Management Review, 2021)
Organizations depend on data, and keeping data safe from cyberattacks can't be just the domain of IT anymore. Companies need a clear, comprehensive cyber resilience plan for managing all aspects of data and setting cross-functional responsibilities for keeping that data safe. This article outlines the key players and their responsibilities in taking a proactive, cross-functional approach to corporate cybersecurity.